The Bible and the Buddhists. J. Duncan M. Derrett. - Lindtner, Chr. (Buddhist Studies Review, 2001)
The Bible and the Buddhists. J. Duncan M. Derrett. Sardini Editrice, Bornato in Franciacorta - Italy 2000. 136 pp. Lire 50,000. ISBN 88-7506-174-2 Pb.